The Church in the face of crisis "Nothing that is genuinely human fails to find an echo in our hearts" (GS, 1) - Mora Rosado, Sebastián (Razón y fe, 2018)
The process of increasing deterioration of social cohesion in which we are immersed has caused important changes in the social and economic reality of Spain. Especially in that of those households that were in a vulnerable situation before the crisis. Faced with the crisis, the Church, as well as other social organizations, has shown immense solidarity with poor and excluded families and people. Convinced, in this Year of Faith, of the inseparable unity of the proclamation of the wonders of the Lord and solidarity with the most vulnerable, the Church has been an intense and creative response to the crisis. In the words of the Porta fidei letter, "Faith without charity bears no fruit, while charity without faith would be a sentiment constantly at the mercy of doubt" (n. 14).